2012
DOI: 10.1007/s10896-011-9409-x
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Police Response to Domestic Violence: A Comparison of College Students in Three Chinese Societies

Abstract: While a large amount of research has been conducted in the West on domestic violence related issues, only a small number of studies have focused specifically on Chinese societies. Using survey data collected from Beijing, Hong Kong, and Taipei, this study compares college students' preferences for traditional and proactive police intervention into domestic violence and assesses the determinants of such preferences in the three Chinese societies. The findings indicate that Hong Kong students showed the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 33 publications
2
39
0
Order By: Relevance
“…Another important finding of this study is that the frequency of police response to female-related crime is significantly related to their decision of putting the female victim into custody. In Sun et al’s (2012) study on college students’ preference for police response to DV, they suggested that experience with DV may be an important predictor for police intervention. Our study provides empirical evidence for their assumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important finding of this study is that the frequency of police response to female-related crime is significantly related to their decision of putting the female victim into custody. In Sun et al’s (2012) study on college students’ preference for police response to DV, they suggested that experience with DV may be an important predictor for police intervention. Our study provides empirical evidence for their assumption.…”
Section: Discussionmentioning
confidence: 99%
“…In China, public awareness of women’s rights began at the 1995 United Nations (UN) Conference on Women, which was held in Beijing, China. This conference led to the creation of the first women’s nongovernmental organization (NGO) in the country that focused on DV (Sun et al, 2012). Since then, DV has gained increasing recognition in China from the public, government, media, and scholars (Cao et al, 2014; Howell, 2005; Leung, 2014; Li, 2015; Sun et al, 2012).…”
Section: In Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…Such patriarchal ideology is so deeply embedded in all aspects of their social lives that family violence was often considered a private family issue (Sun et al 2011 ). Although women’s social status has significantly improved since the establishment of the People’s Republic of China in 1949, especially in recent decades, traditional patriarchal ideology still lingers deep in Chinese culture (Sun et al 2012 ). The interests of individual members of the family, particularly vulnerable members such as the elderly, women, and children, can be sacrificed if their interests are in conflict with those of the family as a whole.…”
Section: Support Inadequate For Victims Of Family Violencementioning
confidence: 99%